Secondary Education in COVID Lockdown: More Anxious and Less Creative—Maybe Not? - Patston, Timothy J.; Kennedy, JohnPaul; Jaeschke, Wayne; Kapoor, Hansika; Leonard, Simon N.; Cropley, David H.; Kaufman, James C. (Frontiers in Psychology, 2021)
Secondary education around the world has been significantly disrupted by COVID-19. Students have been forced into new ways of independent learning, often using remote technologies, but without the social nuances and direct teacher interactions of a normal classroom environment. Using data from the School Attitudes Survey—which surveys students regarding the perceived level of difficulty, anxiety level, self-efficacy, enjoyability, subject relevance, and opportunities for creativity with regards to each of their school subjects—this study examines students’ responses to this disruption from two very different schools with two very different experiences of the pandemic. This paper reports on the composite attitudinal profiles of students in the senior secondary levels at each school (Years 10-12, n = 852). The findings challenged our expectation that the increased difficulty and anxiety caused by the disruption would reduce perceived opportunities for creativity. Indeed, our analyses showed that the students at both schools demonstrated generally positive attitudes towards their learning and strongly associated opportunities for creativity with other attitudinal constructs including enjoyability, subject relevance, and self-efficacy. These complex associations made by the students appear to have buffered the impacts of the disruption, and they may even have supported creative resilience.